1998
DOI: 10.1046/j.1469-8137.1998.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical studies of the infection mechanisms of Botrytis fabae II. Host cell wall breakdown

Abstract: Immunoelectron microscopy using the anti-pectin monoclonal antibody JIM 7 confirmed earlier observations that pectin degradation is a primary event in the process of host cell wall breakdown during the development of chocolate spot disease (causal agent : Botrytis fabae (Sard.)) of broad bean. Close examination of infected and noninfected Vicia faba L. leaves indicated a loss of JIM 7-labelling, and therefore, methyl-esterified pectin, from swollen walls of infected and contiguous epidermal cells. Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…fabae interface inside the host tissue, immunolabelled matrix material could be seen to extend through the swollen epidermal and mesophyll cell walls. The mechanism of plant cell wall breakdown and the role of B. fabae extracellular matrices in this process is the subject of the accompanying paper (Cole, Dewey & Hawes, 1998).…”
Section: mentioning
confidence: 99%
“…fabae interface inside the host tissue, immunolabelled matrix material could be seen to extend through the swollen epidermal and mesophyll cell walls. The mechanism of plant cell wall breakdown and the role of B. fabae extracellular matrices in this process is the subject of the accompanying paper (Cole, Dewey & Hawes, 1998).…”
Section: mentioning
confidence: 99%
“…However, given the effect of pectin methylesterification on the physicochemical properties of the walls, they may also have a role in defense against pathogens by influencing the susceptibility of the wall to cell walldegrading enzymes, which in some cases have a major role in pathogenesis (Clark and Lorbeer, 1976;Collmer and Keen, 1986;Cole et al, 1998;De Lorenzo et al, 2001;D'Ovidio et al, 2004). Pectin hydrolysis often occurs in the diseases caused by soft rot bacteria and fungi and appears to be the prerequisite for degradation of other cell wall components (D'Ovidio et al, 2004).…”
mentioning
confidence: 99%
“…These authors showed that cowpea rust (Uromyces vignae) penetrated the cell walls of the non-host, V. faba and that a zone of the plant wall, 0.2 μm wide along the fungal penetration hypha, had reduced pectin and xyloglucan. Similarly, Cole et al (1998) showed by immunoelectron microscopy, using the anti-pectin monoclonal antibody JIM 7, that pectin degradation is a primary event in host cell wall breakdown during the development of chocolate spot of V. faba caused by B. fabae.…”
Section: Enzymesmentioning
confidence: 96%